2021
DOI: 10.1159/000515986
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Value of Renal Dysfunction Addition to the CHA2DS2-Vasc Score for Mortality Prediction in Patients with Acute Coronary Syndrome

Abstract: <b><i>Introduction:</i></b> This study analyzes the usefulness of the CHA2DS2-VASc score for mortality prediction in patients with acute coronary syndromes (ACSs) and evaluates if the addition of renal functional status could improve its predictive accuracy. <b><i>Methods:</i></b> CHA2DS2-VASc score was calculated by using both the original scoring system and adding renal functional status using 3 alternative renal dysfunction definitions (CHA2DS2-VASc-R1: eGFR &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Furthermore, it has been linked to increased mortality rates and has demonstrated a prognostic accuracy comparable to that of the GRACE scores in patients with coronary artery disease [ 30 ] and systolic HF [ 31 ]. Consistent with previous research, our current investigation revealed associations between CHA 2 DS 2 -VASc score and adverse clinical outcomes among patients hospitalized in CICUs with preserved renal function [ [26] , [27] , [28] , [29] , [30] , [31] ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, it has been linked to increased mortality rates and has demonstrated a prognostic accuracy comparable to that of the GRACE scores in patients with coronary artery disease [ 30 ] and systolic HF [ 31 ]. Consistent with previous research, our current investigation revealed associations between CHA 2 DS 2 -VASc score and adverse clinical outcomes among patients hospitalized in CICUs with preserved renal function [ [26] , [27] , [28] , [29] , [30] , [31] ].…”
Section: Discussionsupporting
confidence: 92%
“…Beyond its established role in stroke prediction, the CHA 2 DS 2 -VASc score has proven valuable in predicting cardiovascular outcomes across several disease conditions, regardless of AF status [ [23] , [24] , [25] ]. Notably, in patients with ACS, the CHA 2 DS 2 -VASc score has emerged as a robust predictor of all-cause mortality and cardiovascular events [ [26] , [27] , [28] , [29] ]. Furthermore, it has been linked to increased mortality rates and has demonstrated a prognostic accuracy comparable to that of the GRACE scores in patients with coronary artery disease [ 30 ] and systolic HF [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated that including CKD in known risk scores, increases the predictive value of the score. A modified CHA2DS2-Vasc score including CKD with a different definition showed a better discriminative capacity than the original score in mortality prediction in an ACS patient population[ 42 ].…”
Section: Discussionmentioning
confidence: 99%